Factores de competitividad en la producción y exportación de aguacate Hass en el Valle del Cauca del periodo 2015 a 2019" (2021)
The main objective of this research is to analyze the exports of Hass avocado in Colombia mainly in the Valle del Cauca, during the years 2015 to 2019 the competitive level of the department in this period of time with respect to the rest of the departments in Colombia is studied. However, although the country has an increase in exports, which has shown growth in foreign markets, it is still one of the countries that produces the least avocado for export.